Positron Emission Tomography to Characterize Dorsocervical Fat Pad Hypertrophy in People With Treated HIV Infection. (1st March 2020) - Janus, Scott E.; Sullivan, Claire; Morrison, Justin; McComsey, Grace A.; Longenecker, Chris T.
Abstract : Supplemental Digital Content is Available in the Text.